Acrylic resin, and adhesive composition, adhesive, adhesive film, masking adhesive, and masking adhesive film using the same
Patent Information
- Application Number
- JP2021035503
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-05
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-03-05
Smart Images

Figure 0007635582000001 
Figure 0007635582000002 
Figure 0007635582000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an acrylic resin, and a pressure-sensitive adhesive composition, a pressure-sensitive adhesive, a pressure-sensitive adhesive film, a masking pressure-sensitive adhesive, and a masking pressure-sensitive adhesive film using the same. More specifically, the present invention relates to an acrylic resin that can provide a pressure-sensitive adhesive that has sufficient adhesive strength even when applied to a wet surface, and that has excellent resistance to contamination of the adherend without leaving any adhesive residue on the adherend surface even when used as a masking pressure-sensitive adhesive, and a pressure-sensitive adhesive composition using the same, a pressure-sensitive adhesive such as a masking pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition, and a pressure-sensitive adhesive film such as a masking pressure-sensitive adhesive film having a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive. [Background technology]
[0002] In recent years, adhesive tapes have been used in various industrial fields such as home appliances, automobiles, office automation equipment, and construction as a joining means with good workability and high adhesive reliability. In addition, there has been a demand for adhesives that can provide sufficient adhesive performance even under water or wet conditions. However, it is generally difficult to obtain sufficient adhesive performance when the surface of the object to be bonded is wet.
[0003] Under these circumstances, for example, Patent Document 1 discloses a water-dispersible pressure-sensitive adhesive composition and pressure-sensitive adhesive product that can exhibit good initial adhesive strength on condensation-covered or wet surfaces and has excellent constant-load peelability, the water-dispersible pressure-sensitive adhesive composition being characterized in that it contains 0.5 to 15 parts by weight of a specific hydrophilic polymer per 100 parts by weight of the solid content in the acrylic or rubber-based water-dispersible pressure-sensitive adhesive composition.
[0004] However, the pressure-sensitive adhesive composition disclosed in Patent Document 1 is an aqueous dispersion type pressure-sensitive adhesive composition that uses a water-soluble resin as a dispersant, and therefore, when used in water or under humid conditions for a long period of time, the pressure-sensitive adhesive may dissolve in water and may not be able to maintain its adhesive performance.
[0005] Patent Document 2 discloses an adhesive sheet for application to wet surfaces that can reliably and easily place an object to be attached on a wet surface, and that has a water-absorbing layer on one side of the adhesive layer, and by creating gaps in the adhesive layer, moisture on the wet surface is absorbed by the water-absorbing layer, thereby exhibiting good adhesive strength. However, because there are gaps in the adhesive layer, the adhesive strength may decrease.
[0006] Furthermore, the technologies disclosed in Patent Documents 1 and 2 above do not take into consideration at all the contamination resistance of the adherend, that is, preventing adhesive residue and the occurrence of adhesive marks on the surface of the adherend when the adhesive is used as a temporary protective (masking) adhesive, adhered to the adherend, and then peeled off. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2003-313525 A [Patent Document 2] JP 2017-160344 A Summary of the Invention [Problem to be solved by the invention]
[0008] In view of the above, the present invention aims to provide an acrylic resin that has sufficient adhesive strength even when applied to a wet surface, and that, when used as a masking adhesive, makes it possible to obtain an adhesive that leaves no adhesive residue on the surface of the adherend and has excellent resistance to contamination of the adherend. Another aim of the present invention is to provide an adhesive composition, an adhesive, an adhesive film, an adhesive for masking, and an adhesive film for masking, each using such an acrylic resin. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to solve the above problems. In the course of their research, they have found that the adhesive performance in water or under wet conditions can be improved by using a copolymerization component (a) constituting the acrylic resin (A), which is a material of the adhesive composition, that is mainly composed of a (meth)acrylic acid alkyl ester monomer (a3) having an alkyl group with 1 to 20 carbon atoms, in combination with a small amount of a copolymerizable monomer (a2) having a hydroxyl group and / or a carboxyl group, and a specific acrylic monomer (a1) represented by general formula (1), and have arrived at the present invention.
[0010] Therefore, the gist of the present invention is the following [1] to [8]. [1] An acrylic resin (A) obtained by copolymerizing a copolymerization component (a) containing 0.01 to 50% by weight of an acrylic monomer (a1) represented by the following general formula (1), 0.1 to 30% by weight of a copolymerizable monomer (a2) having a hydroxyl group and / or a carboxy group excluding the above (a1), and 40 to 99% by weight of a (meth)acrylic acid alkyl ester monomer (a3) having an alkyl group having 1 to 20 carbon atoms: [ka] [2] The acrylic resin (A) according to [1], wherein R3 in the general formula (1) is a molecular chain having at least one structure selected from the group consisting of a ketone structure, an ester structure, and a hydrocarbon structure. [3] The acrylic resin (A) according to [1] or [2], wherein the copolymerizable monomer (a2) having a hydroxyl group and / or a carboxyl group is (meth)acrylic acid and / or a (meth)acrylate monomer. [4] A pressure-sensitive adhesive composition comprising the acrylic resin (A) according to any one of [1] to [3] and a crosslinking agent (B). [5] A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition described in [4]. [6] An adhesive film having an adhesive layer made of the adhesive described in [5]. [7] A masking adhesive, characterized by using the adhesive described in [5]. [8] A masking adhesive film having an adhesive layer made of the adhesive described in [5]. Effect of the Invention
[0011] The acrylic resin (A) of the present invention has sufficient adhesive strength even when applied to a wet surface, and when used as a masking adhesive, it is possible to obtain an adhesive that leaves no adhesive residue on the surface of the adherend and has excellent resistance to contamination of the adherend. Therefore, the adhesive composition, adhesive, adhesive film, masking adhesive, and masking adhesive film made using the above acrylic resin can exhibit excellent adhesive performance when used in water or under wet conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below, but these are merely examples of preferred embodiments. In addition, "(meth)acrylic" means acrylic or methacrylic, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylate" means acrylate or methacrylate. In addition, "acrylic resin" is a resin obtained by polymerizing a polymerization component containing at least one (meth)acrylate monomer. In addition, the "adhesive" in this invention is one that has tack at 25°C (room temperature) and adheres to an adherend with light pressure, such as that applied by hand, and the "film" conceptually encompasses sheets, films, and tapes.
[0013] <Acrylic resin (A)> As described above, the acrylic resin (A) of the present invention is obtained by copolymerizing a copolymerization component (a) containing 0.01 to 50% by weight of an acrylic monomer (a1) represented by the following general formula (1), 0.1 to 30% by weight of a copolymerizable monomer (a2) having a hydroxyl group and / or a carboxy group excluding the above (a1), and 40 to 99% by weight of a (meth)acrylic acid alkyl ester monomer (a3) having an alkyl group having 1 to 20 carbon atoms.
[0014] [ka]
[0015] The copolymerization components (a) of the acrylic resin (A), that is, the acrylic monomer (a1) represented by the above general formula (1) (hereinafter, sometimes simply referred to as monomer (a1)), the copolymerizable monomer (a2) having a hydroxyl group and / or a carboxyl group excluding the above (a1) (hereinafter, sometimes simply referred to as monomer (a2)), the (meth)acrylic acid alkyl ester monomer (a3) having an alkyl group having 1 to 20 carbon atoms (hereinafter, sometimes simply referred to as monomer (a3)), and the other monomer (a4) which is an optional component (hereinafter, sometimes simply referred to as monomer (a4)) will be described in order below.
[0016] [Monomer (a1)] The monomer (a1) is an acrylic monomer represented by the following general formula (1).
[0017] [ka]
[0018] In the above general formula (1), R1 is H- or CH3-, preferably CH3-. R2 is -O- or -NH-, preferably -O-. R3 is a molecular chain, preferably a molecular chain having at least one selected from the group consisting of a ketone structure (-C(=O)-), an ester structure (-O-C(=O)-, -C(=O)-O-), and a hydrocarbon structure. Among them, a molecular chain having a ketone structure (-C(=O)-) and an ester structure (-O-C(=O)-, -C(=O)-O-) is more preferable. R3 is usually a molecular chain having 1 to 5 carbon atoms, preferably a molecular chain having 1 to 3 carbon atoms. n is an integer of 2 to 5, preferably 2 or 3. The monomer (a1) preferably has a catechol group or a gallol group. That is, when R1 to R3 and n are specified as above, the adhesive strength when applied to a wet surface is improved.
[0019] The monomer represented by the above general formula (1) is specifically the monomer represented by the following chemical formulas (1-a) to (1-e) (acrylic monomers (1-a) to (1-e)) used alone or in combination of two or more. Among them, the monomer represented by the chemical formulas (1-a) and (1-b) (acrylic monomer (1-a) and acrylic monomer (1-b) are preferred because they provide better adhesion performance in water or under wet conditions as required by the present invention.
[0020] [ka]
[0021] [ka]
[0022] [ka]
[0023] [ka]
[0024] [ka]
[0025] In the monomer (a1) constituting the acrylic resin (A), the acrylic monomers (1-a) to (1-e) may be used alone or in combination. From the viewpoint of improving the adhesive performance in water or under wet conditions required in the present invention, the total proportion of the acrylic monomers (1-a) to (1-e) relative to the entire copolymerization component (a) is preferably 0.01 to 50% by weight, more preferably 0.1 to 40% by weight, even more preferably 0.5 to 30% by weight, and particularly preferably 0.9 to 20% by weight.
[0026] From the viewpoint of improving the adhesive performance in water or under wet conditions required in the present invention, the total proportion of the acrylic monomers (1-a) to (1-e) in the acrylic resin (A) is preferably 0.01 to 50 mol %, more preferably 0.05 to 20 mol %, even more preferably 0.1 to 10 mol %, and particularly preferably 0.5 to 3 mol %.
[0027] The acrylic monomers (1-a) to (1-e) can be produced, for example, as follows.
[0028] [Production of acrylic monomer (1-a)] The acrylic monomer (1-a) can be synthesized, for example, by obtaining methanesulfonate-2-ethyl methacrylate by mesylation of 2-hydroxyethyl methacrylate, and then reacting the methanesulfonate-2-ethyl methacrylate with gallic acid, as shown in the following reaction formula.
[0029] [ka]
[0030] The mesylation of 2-hydroxyethyl methacrylate is carried out by dissolving the 2-hydroxyethyl methacrylate in a solvent such as tetrahydrofuran to obtain a mixture with triethylamine, and then adding methanesulfonyl chloride to the mixture to cause a reaction. The blending molar ratio of 2-hydroxyethyl methacrylate to methanesulfonyl chloride is 2-hydroxyethyl methacrylate:methanesulfonyl chloride=about 1:1.1 to 1:1.3.
[0031] By removing the solvent from the mixed solution after the above reaction, methanesulfonate-2-ethyl methacrylate (yellow liquid) can be obtained.
[0032] In addition, the above-mentioned yellow liquid 1 The results of the H NMR analysis are as follows: 1 H NMR (400MHz, CDCl3): δ=6.08(s, 1H), 5.57-5.54(m, 1H), 4.41-4.37(m, 2H), 4.35-4.31(m, 2H), 2.98(s, 3H), 1.88(s, 3H)
[0033] Next, a solution of gallic acid, sodium bicarbonate, and dimethyl sulfoxide (DMSO) is prepared, and methanesulfonate-2-ethyl methacrylate is added and reacted. The blending molar ratio of methanesulfonate-2-ethyl methacrylate and gallic acid is methanesulfonate-2-ethyl methacrylate:gallic acid=about 1:1.1 to 1:1.3. Thereafter, the solvent is removed, the residue is purified by column chromatography, and then recrystallized from a solution of ethyl acetate / n-heptane to obtain the acrylic monomer (1-a) (white solid).
[0034] In addition, the above white solid 1 The results of the H NMR analysis are as follows: 1 H NMR (400MHz, DMSO-d6): δ=9.22(s, 3H), 6.94(s, 2H), 6.05-6.02(m, 1H), 5.71-5.67(m, 1H), 4.46-4.36(m, 4H), 1.87(t, 3H)
[0035] [Production of acrylic monomer (1-b)] The acrylic monomer (1-b) can be synthesized, for example, by reacting 4-(chloroacetyl)catechol with methacrylic acid as shown in the following formula.
[0036] [ka]
[0037] 4-(Chloroacetyl)catechol methacrylic acid and methacrylic acid are dissolved in a solvent such as acetonitrile to obtain a mixed solution. Triethylamine is added to the resulting mixed solution to cause a reaction. The molar ratio of methacrylic acid to 4-(chloroacetyl)catechol is about 1:0.4 to 1:0.6 (methacrylic acid:4-(chloroacetyl)catechol). The solvent is removed from the mixed solution after the reaction, and the resulting solution is purified by column chromatography to obtain the acrylic monomer (1-b) (white solid).
[0038] In addition, the above white solid 1 The results of the H NMR analysis are as follows: 1 H NMR (400MHz, DMSO-d6): δ=10.45-9.27(m, 2H), 7.43-7.28(m, 2H), 6.84(d, 1H), 6.12(s, 1H), 5.77(t, 1H), 5.42(s, 2H), 1.93(s, 3H)
[0039] [Production of acrylic monomer (1-c)] The acrylic monomer (1-c) can be synthesized, for example, by reacting dopamine hydrochloride with methacrylic anhydride as shown in the following formula.
[0040] [ka]
[0041] Dissolve sodium bicarbonate and sodium tetraborate decahydrate in a solvent such as water (1000 mL) to prepare a solution, then add dopamine hydrochloride, and add a mixture of methacrylic anhydride and a solvent such as tetrahydrofuran (250 mL) dropwise to the above solution to react. The molar ratio of methacrylic anhydride to dopamine hydrochloride is methacrylic anhydride:dopamine hydrochloride=about 1:0.8 to 1:1. Next, the reaction solution is filtered and the solvent is replaced to give an ethyl acetate solution, which is then precipitated by recrystallization to give the acrylic monomer (1-c) (white solid).
[0042] In addition, the above white solid 1 The results of the H NMR analysis are as follows: 1 H NMR(400MHz,DMSO-d6): δ=8.78-8.73(m, 1H), 8.66-8.61(m, 1H), 7.94(t, 1H), 6.62(d, 1H), 6.57(d, 1H), 6.42 (dd, 1H), 5.61(s, 1H), 5.29(t, 1H), 3.25-3.18(m, 2H), 2.58-2.53(m, 2H), 1.83(s, 3H)
[0043] [Production of acrylic monomer (1-d)] The acrylic monomer (1-d) can be synthesized, for example, by reacting methanesulfonate-2-ethyl methacrylate with 3,4-dihydroxybenzoic acid as shown in the following formula.
[0044] [ka]
[0045] 3,4-Dihydroxybenzoic acid is dissolved in a solvent such as DMSO, and methanesulfonate-2-ethyl methacrylate obtained in the same manner as for the acrylic monomer (1-a) and sodium bicarbonate are added to react with each other. The blending molar ratio of such methanesulfonate-2-ethyl methacrylate and 3,4-dihydroxybenzoic acid is methanesulfonate-2-ethyl methacrylate:3,4-dihydroxybenzoic acid=about 1:1.1 to 1:1.3. Thereafter, a polymerization inhibitor is added, the solvent is removed, and the reaction mixture is recrystallized from a solution of acetonitrile / n-heptane=10 / 1, thereby obtaining the above acrylic monomer (1-d) (white solid).
[0046] The above white solid 1 The results of the H NMR analysis are as follows: 1 H NMR (400MHz, DMSO-d6): δ=9.59(s, 2H), 7.38-7.24(m, 2H), 6.82-6.80(d, 1H), 6.03(s, 1H), 5.68(s, 1H), 4.48-4.36(m, 4H), 1.86(s, 3H)
[0047] [Production of acrylic monomer (1-e)] The acrylic monomer (1-e) can be synthesized, for example, by reacting 3,4-dihydroxybenzaldehyde according to the following formula:
[0048] [ka]
[0049] The above-mentioned acrylic monomer (1-e) using 3,4-dihydroxybenzaldehyde can be obtained by carrying out "protection of the hydroxyl group of 3,4-dihydroxybenzaldehyde", "reduction reaction of 3,4-bis(1-ethoxyethoxy)benzaldehyde", "methacrylation of 3,4-bis(1-ethoxyethoxy)benzyl alcohol", and "deprotection of the 1-ethoxyethoxy group".
[0050] "Protection of hydroxyl groups in 3,4-dihydroxybenzaldehyde" 3,4-Dihydroxybenzaldehyde and pyridinium p-toluenesulfonate are dissolved in dichloromethane, and ethyl vinyl ether is added and reacted. The molar ratio of 3,4-dihydroxybenzaldehyde to ethyl vinyl ether is 3,4-dihydroxybenzaldehyde:ethyl vinyl ether=about 1:1.8 to 1:2.5. Thereafter, the solvent is removed from the reaction solution to obtain 3,4-bis(1-ethoxyethoxy)benzaldehyde (a brown oily liquid).
[0051] In addition, the above-mentioned brown oily liquid 1 The results of the H NMR analysis are as follows: 1 H NMR(400MHz,CDCl3): δ=9.84(s, 1H), 7.56(t, 1H), 7.48(dt, 1H), 7.21(dd, 1H), 5.50(qd, 1H), 5.42-5.35 (m, 1H), 3.90-3.74(m, 2H), 3.63-3.50(m, 2H), 1.56-1.48(m, 6H), 1.23-1.15(m, 6H)
[0052] "Reduction of 3,4-bis(1-ethoxyethoxy)benzaldehyde" The above 3,4-bis(1-ethoxyethoxy)benzaldehyde is dissolved in a solvent such as tetrahydrofuran (900 mL) to obtain a solution, which is then reacted with sodium borohydride. The molar ratio of 3,4-bis(1-ethoxyethoxy)benzaldehyde to sodium borohydride is 3,4-bis(1-ethoxyethoxy)benzaldehyde:sodium borohydride=about 1:0.9 to 1:1.1. Thereafter, the solvent is removed from the reaction solution obtained as described above to obtain 3,4-bis(1-ethoxyethoxy)benzyl alcohol (yellow oily liquid).
[0053] In addition, the above-mentioned yellow oily liquid 1 The results of the H NMR analysis are as follows: 1 H NMR(400MHz,CDCl3): δ=7.10-7.03(m, 2H), 6.93(dt, 1H), 5.38-5.30(m, 2H), 4.58(s, 2H), 3.8 9-3.79(m, 2H), 3.62-3.51(m, 2H), 1.50-1.47(m, 6H), 1.23-1.16(m, 6H)
[0054] "Methacrylation of 3,4-bis(1-ethoxyethoxy)benzyl alcohol" The above 3,4-bis(1-ethoxyethoxy)benzyl alcohol, triethylamine and 4-dimethylaminopyridine are added and dissolved in tetrahydrofuran or the like, and then reacted with methacrylic anhydride (55.3 g, 0.36 mol). The blending molar ratio of such 3,4-bis(1-ethoxyethoxy)benzyl alcohol to methacrylic anhydride is 3,4-bis(1-ethoxyethoxy)benzyl alcohol:methacrylic anhydride=about 1:0.9 to 1:1.1. After the reaction, the solvent is removed by an evaporator, and the resulting product is purified by column chromatography to obtain a 1-ethoxyethoxy protected product of the acrylic monomer (1-e) (white solid).
[0055] In addition, the above-mentioned white solid 1 The results of the H NMR analysis are as follows: 1H NMR(400MHz,CDCl3): δ=7.12(d, 1H), 7.06(d, 1H), 6.99-6.95(m, 1H), 6.14(s, 1H), 5.60-5.56(m, 1H), 5.40-5.30(m, 2H), 5 .11(s, 2H), 3.91-3.77(m, 2H), 3.64-3.53(m, 2H), 1.96(s, 3H), 1.54-1.46(m, 6H), 1.24-1.17(m, 6H)
[0056] "Deprotection of 1-ethoxyethoxy group" The 1-ethoxyethoxy protected acrylic monomer (1-e) is dissolved in a solvent such as methanol and reacted with pyridinium p-toluenesulfonate. After the reaction, the solvent is removed and the product is purified by column chromatography to obtain the acrylic monomer (1-e) (white solid).
[0057] In addition, the above-mentioned white solid 1 The results of the H NMR analysis are as follows: 1 H NMR (400MHz, CDCl3): δ=6.92(d, 1H), 6.88-6.81(m, 2H), 6.16(s, 1H), 6.04-5.75(m, 3H), 5.09(s, 2H), 1.96(s, 3H)
[0058] [Monomer (a2)] The copolymerizable monomer (a2) having a hydroxyl group and / or a carboxyl group may be used alone or in combination of two or more kinds. From the viewpoint of adhesion to the adherend, the monomer (a2) is preferably a copolymerizable monomer having a carboxyl group, more preferably (meth)acrylic acid or a (meth)acrylate monomer having a carboxyl group. In particular, (meth)acrylic acid is preferred.
[0059] Examples of copolymerizable monomers having a hydroxyl group include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; caprolactone-modified monomers such as caprolactone-modified 2-hydroxyethyl (meth)acrylate; oxyalkylene-modified monomers such as diethylene glycol (meth)acrylate and polyethylene glycol (meth)acrylate; primary hydroxyl group-containing monomers such as 2-acryloyloxyethyl-2-hydroxyethyl phthalate; secondary hydroxyl group-containing monomers such as 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 3-chloro 2-hydroxypropyl (meth)acrylate; and tertiary hydroxyl group-containing monomers such as 2,2-dimethyl 2-hydroxyethyl (meth)acrylate. Among these, primary hydroxyl group-containing monomers are preferred because of their excellent reactivity with crosslinking agents, and 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are particularly preferred.
[0060] Furthermore, examples of copolymerizable monomers having a carboxy group include (meth)acrylic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxypropyl phthalic acid, 2-(meth)acryloyloxyethyl maleic acid, 2-(meth)acryloyloxypropyl maleic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxypropyl succinic acid, crotonic acid, fumaric acid, maleic acid, itaconic acid, monomethyl maleate, and monomethyl itaconate. Among these, acrylic acid is preferred from the standpoint of adhesion and stability during polymerization.
[0061] The proportion of the monomer (a2) relative to the total copolymerization components (a) constituting the acrylic resin (A) is preferably 0.1 to 30% by weight, more preferably 0.5 to 25% by weight, even more preferably 1 to 20% by weight, and particularly preferably 3 to 15% by weight.
[0062] [Monomer (a3)] As the (meth)acrylic acid alkyl ester monomer (a3), a (meth)acrylic acid alkyl ester monomer having an alkyl group having 1 to 20 carbon atoms is usually used, preferably a (meth)acrylic acid alkyl ester monomer having an alkyl group having 2 to 10 carbon atoms, and more preferably a (meth)acrylic acid alkyl ester monomer having an alkyl group having 4 to 8 carbon atoms. Specific examples of the monomer (a3) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isodecyl (meth)acrylate, tridecyl (meth)acrylate, n-lauryl (meth)acrylate, etc. Among these, n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred from the viewpoints of excellent adhesive properties and excellent stability during polymerization, and n-butyl acrylate is more preferred. These monomers can be used alone or in combination of two or more kinds.
[0063] The proportion of the monomer (a3) relative to the total copolymerization components (a) constituting the acrylic resin (A) is 40 to 99% by weight, preferably 50 to 98% by weight, more preferably 70 to 97% by weight, and even more preferably 80 to 95% by weight.
[0064] [Monomer (a4)] Moreover, a monomer (a4) other than (a1) to (a3) may be optionally contained within a range that does not impair the effects of the present invention. For example, acid anhydride group-containing vinyl monomers such as maleic anhydride and itaconic anhydride; epoxy group-containing vinyl monomers such as glycidyl (meth)acrylate, glycidyl α-ethyl acrylate, and 3,4-epoxybutyl (meth)acrylate; amino group-containing (meth)acrylate vinyl monomers such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; (meth)acrylamide, Nt-butyl (meth)acrylamide, N-methylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, diacetone acrylamide, and maleic acid amine. vinyl monomers containing an amide group, such as maleimide and styrene; vinyl monomers such as styrene, α-methylstyrene, vinyl toluene, (meth)acrylonitrile, vinyl chloride, vinyl acetate, and vinyl propionate; divinylbenzene, ethylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and allyl (meth)acrylate. The other monomers (a4) may be used alone or in combination of two or more kinds.
[0065] The content of the monomer (a4) relative to the total copolymerization component (a) constituting the acrylic resin (A) is preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 1% by weight or less.
[0066] [Production of acrylic resin (A)] The acrylic resin (A) used in the present invention can be produced by polymerizing the copolymerization component (a) containing the specific acrylic monomers (1-a) to (1-e) and other monomers by, for example, mixing or dropping a polymerization initiator into an organic solvent.
[0067] The polymerization reaction can be carried out by a conventionally known polymerization method such as solution radical polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc., and among these, solution radical polymerization and bulk polymerization are preferred, and solution radical polymerization is more preferred.
[0068] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbons such as toluene and xylene, aliphatic hydrocarbons such as hexane, esters such as ethyl acetate and butyl acetate, aliphatic alcohols such as n-propyl alcohol and isopropyl alcohol, and ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone.
[0069] Among these organic solvents, ethyl acetate, acetone, methyl ethyl ketone, butyl acetate, toluene, and methyl isobutyl ketone are preferably used, and more preferably ethyl acetate, acetone, and methyl ethyl ketone, in view of the ease of polymerization reaction, the effect of chain transfer, the ease of drying during adhesive coating, and high safety. These organic solvents may be used alone or in combination of two or more kinds. The amount of these organic solvents used is usually 10 to 900 parts by weight per 100 parts by weight of the copolymerization component (a) constituting the acrylic resin (A).
[0070] In addition, examples of the polymerization initiator used in such solution radical polymerization include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 4,4'-azobis(4-cyanovaleric acid), and 2,2'-azobis(methylpropionic acid), which are normal radical polymerization initiators, and organic peroxides such as benzoyl peroxide, lauroyl peroxide, di-t-butyl peroxide, and cumene hydroperoxide, which can be appropriately selected and used according to the monomer to be used. Among them, 2,2'-azobisisobutyronitrile is preferred in the present invention. These polymerization initiators may be used alone or in combination of two or more. The amount of these polymerization initiators used is usually 0.01 to 5% by weight based on the copolymerization component (a).
[0071] [Physical properties of acrylic resin (A)] The weight average molecular weight (Mw) of the acrylic resin (A) thus obtained is preferably 100,000 to 3,000,000, more preferably 200,000 to 2,000,000, even more preferably 300,000 to 1,800,000, and particularly preferably 350,000 to 1,600,000. If the weight average molecular weight is too small, durability tends to decrease, whereas if it is too large, a large amount of dilution solvent is required during preparation, drying properties decrease, and residual solvent increases in the pressure-sensitive adhesive layer, tending to decrease durability.
[0072] The dispersity (weight average molecular weight / number average molecular weight) of the acrylic resin (A) is preferably 30 or less, more preferably 20 or less, and further preferably 15 or less. If the degree of dispersion is too high, reworkability and durability tend to decrease. The lower limit of the degree of dispersion is usually 1.
[0073] The weight-average molecular weight (Mw) is the weight-average molecular weight calculated based on the molecular weight of standard polystyrene. The high-performance liquid chromatograph (Waters Corporation, "Waters 2695 (main body)" and "Waters 2414 (detector)") was equipped with a Shodex GPC KF-806L column (molecular weight exclusion limit: 2 × 10 7 , Separation range: 100~2×10 7 The measurement is performed by connecting three tubes in series: theoretical plate number: 10,000 plates / tube, filler material: styrene-divinylbenzene copolymer, filler particle size: 10 μm. The number average molecular weight is also measured in the same way, and the dispersity (weight average molecular weight / number average molecular weight) is calculated from the number average molecular weight and weight average molecular weight.
[0074] The glass transition temperature (Tg) of the acrylic resin (A) is preferably -70°C or higher, more preferably -60 to 10°C, even more preferably -55 to 0°C, and particularly preferably -52 to -10°C, from the standpoints of adhesive performance and contamination resistance of the adherend.
[0075] The glass transition temperature (Tg) of the acrylic resin (A) is a value measured using a differential scanning calorimeter "DSC Q2000" manufactured by TA Instruments, Inc. The measurement temperature range is -80 to 40°C, and the temperature rise rate is 5°C / min.
[0076] [Acrylic resin (A) solution] The acrylic resin (A) is usually adjusted in viscosity with a solvent or the like, and used in the pressure-sensitive adhesive composition of the present invention as a solution of the acrylic resin (A). The dilution concentration is preferably 5 to 60% by weight, more preferably 10 to 50% by weight, and even more preferably 30 to 45% by weight in terms of resin content. If the concentration is too high, the fluidity tends to decrease, making it difficult to handle, and if the concentration is too low, it tends to be difficult to apply the pressure-sensitive adhesive.
[0077] The viscosity of the acrylic resin (A) solution is preferably 100 to 30,000 mPa·s, more preferably 500 to 20,000 mPa·s, further preferably 1,000 to 15,000 mPa·s, and particularly preferably 1,300 to 10,000 mPa·s, from the viewpoint of ease of handling. If the viscosity is too high, the fluidity decreases and handling tends to become difficult, whereas if the viscosity is too low, application of the resulting adhesive tends to become difficult. The viscosity of the acrylic resin (A) solution is measured by subjecting the resin solution, whose temperature has been adjusted to 25° C., to a rotational viscosimetry using a Brookfield viscometer.
[0078] <Adhesive composition> In order to improve adhesive residual properties and the durability of the adhesive, it is preferable that the pressure-sensitive adhesive composition of the present invention further contains a crosslinking agent (B) in addition to the acrylic resin (A).
[0079] [Crosslinking agent (B)] The crosslinking agent (B) used in the pressure-sensitive adhesive composition of the present invention reacts with the functional groups in the acrylic resin (A) to form a crosslinked structure, and examples thereof include epoxy-based crosslinking agents, isocyanate-based crosslinking agents, aziridine-based crosslinking agents, melamine-based crosslinking agents, aldehyde-based crosslinking agents, amine-based crosslinking agents, metal chelate-based crosslinking agents, etc. Among these, it is preferable to use an epoxy-based crosslinking agent because of its excellent adhesive performance and pot life. The crosslinking agent (B) may be used alone or in combination of two or more kinds.
[0080] Examples of the epoxy crosslinking agent include bisphenol A-epichlorohydrin type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl erythritol, diglycerol polyglycidyl ether, 1,3'-bis(N,N-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidyl-m-xylylenediamine. Among these epoxy crosslinking agents, polyfunctional epoxy resins such as 1,3'-bis(N,N-diglycidylaminomethyl)cyclohexane and N,N,N',N'-tetraglycidyl-m-xylylenediamine are preferred in terms of high reactivity.
[0081] Examples of the isocyanate-based crosslinking agent include aromatic isocyanate-based crosslinking agents such as tolylene diisocyanate-based crosslinking agents such as 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, xylylene diisocyanate-based crosslinking agents such as 1,3-xylylene diisocyanate, diphenylmethane-4,4-diisocyanate and other diphenylmethane-based crosslinking agents, and naphthalene diisocyanate-based crosslinking agents such as 1,5-naphthalene diisocyanate; isophorone diisocyanate, 1,4-cyclohexane diisocyanate, and other diphenylmethane-based crosslinking agents. alicyclic isocyanate crosslinking agents such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and the like; and adducts, biuret forms, and isocyanurates of the above-mentioned isocyanate compounds. Among these isocyanate-based crosslinking agents, tolylene diisocyanate-based crosslinking agents are preferred in terms of pot life and durability, xylylene diisocyanate-based crosslinking agents or isocyanurate skeleton-containing isocyanate-based crosslinking agents are preferred in terms of shortening the aging time, and aromatic ring-free isocyanate-based crosslinking agents are preferred in terms of yellowing resistance. Specifically, among these, tolylene diisocyanate, xylylene diisocyanate, an adduct of hexamethylene diisocyanate and trimethylolpropane, and a nurate are preferred in terms of excellent balance between durability, pot life, and crosslinking speed.
[0082] Examples of the aziridine-based crosslinking agent include tetramethylolmethane-tri-β-aziridinylpropionate, trimethylolpropane-tri-β-aziridinylpropionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), and N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide).
[0083] Examples of the melamine-based crosslinking agent include hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, hexaptoxymethylmelamine, hexapentyloxymethylmelamine, hexahexyloxymethylmelamine, melamine resins, and the like.
[0084] Examples of the aldehyde crosslinking agent include glyoxal, malondialdehyde, succindialdehyde, maleic dialdehyde, glutaric dialdehyde, formaldehyde, acetaldehyde, and benzaldehyde.
[0085] Examples of the amine-based crosslinking agent include hexamethylenediamine, triethyldiamine, polyethyleneimine, hexamethylenetetraamine, diethylenetriamine, triethyltetraamine, isophoronediamine, amino resins, and polyamides.
[0086] Examples of the metal chelate crosslinking agent include coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium with acetylacetone or acetoacetyl ester.
[0087] When such a crosslinking agent (B) is used, its content is preferably 0.001 to 20 parts by weight, more preferably 0.01 to 15 parts by weight, even more preferably 0.05 to 10 parts by weight, and particularly preferably 0.09 to 5 parts by weight, relative to 100 parts by weight of the acrylic resin (A). If the content is too low, the removability tends to be easily reduced, whereas if the content is too high, the adhesion to the adherend tends to be reduced or long-term aging is required.
[0088] <Other ingredients> The pressure-sensitive adhesive composition of the present invention may contain other known additives, such as polyether compounds such as polyalkylene glycols such as polypropylene glycol, colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, antiaging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particulate materials, foil-like materials, etc., which can be appropriately added depending on the application. In addition, a redox system in which a reducing agent is added may be adopted within a controllable range. These can be used alone or in combination of two or more. The amount of these additives is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, and further preferably 1 part by weight or less, based on 100 parts by weight of the acrylic resin (A).
[0089] Thus, the pressure-sensitive adhesive composition of the present invention can be obtained by mixing the acrylic resin (A), preferably further the crosslinking agent (B), and further other optional components as required.
[0090] From the viewpoints of adhesion, removability, etc., the proportion of the acrylic resin (A) in the entire pressure-sensitive adhesive composition of the present invention is preferably 50% by weight or more, more preferably 60% by weight or more, even more preferably 70% by weight or more, and particularly preferably in the range of 80 to 99.9% by weight.
[0091] The mixing method is not particularly limited, and various methods can be used, such as a method of mixing the components all at once, or a method of mixing any of the components and then mixing the remaining components all at once or sequentially.
[0092] <Adhesive> The adhesive composition of the present invention becomes an adhesive by drying and / or crosslinking. Such an adhesive has sufficient adhesive strength even when applied to a wet surface, and when used as an adhesive for masking, it is an adhesive that has excellent resistance to contamination of the adherend without leaving any adhesive residue on the adherend surface. Therefore, it can be suitably used as an adhesive for various members such as an adhesive for masking films, an adhesive for surface protection films, an adhesive for display labels, and an adhesive for masking tapes, and is particularly suitable for use as an adhesive for masking films, particularly as an adhesive for architectural masking films. In forming such a pressure-sensitive adhesive layer, when the crosslinking agent (B) is used, it is preferable to adjust the total amount of the crosslinking agent (B) added and to fully consider the effects of the crosslinking temperature and time.
[0093] The crosslinking temperature and time can be adjusted depending on the crosslinking agent (B) used. The crosslinking temperature is preferably 170° C. or less.
[0094] <Adhesive layer> The adhesive can be laminated as an adhesive layer on various substrates. The thickness of the adhesive layer is preferably 5 to 300 μm, more preferably 10 to 200 μm, and even more preferably 20 to 150 μm. If the adhesive layer is too thin, the thickness precision tends to decrease and the adhesive strength tends to decrease, and if it is too thick, the adhesive film tends to protrude from the edge when rolled.
[0095] The gel fraction of the pressure-sensitive adhesive layer is preferably 0.1 to 99% by weight, more preferably 1 to 90% by weight, and even more preferably 10 to 80% by weight, from the viewpoints of adhesion to the substrate, reworkability, and holding power. If the gel fraction is too low, the cohesive strength is low, and there is a tendency for adhesive residue to remain during rework and for holding power to be low, whereas if the gel fraction is too high, there is a tendency for the adhesive strength to be too low and for the adhesive to be easily peeled off.
[0096] The gel fraction is a measure of the degree of crosslinking (degree of curing) and is calculated, for example, by the following method: An adhesive is picked from an adhesive film having an adhesive layer formed on a substrate, the adhesive is wrapped in a 200-mesh SUS wire netting and immersed in toluene at 23°C for 24 hours, and the weight percentage of the insoluble adhesive component remaining in the wire netting relative to the weight of the adhesive before immersion in toluene is defined as the gel fraction.
[0097] The pressure-sensitive adhesive layer preferably has a moderate tackiness when touched with a finger, since this tends to improve workability due to good wettability when actually applied to an adherend. Tackiness is measured by ball tack at an inclination angle of 30° as specified in JIS Z0237 (2009). Ball tackiness is preferably 1 or more, more preferably 3 or more. If the ball tackiness is too low, the pressure-sensitive adhesive film tends to be difficult to adhere to the adherend when it is applied to the adherend.
[0098] <Adhesive film> The pressure-sensitive adhesive film of the present invention is obtained by laminating the pressure-sensitive adhesive layer on a substrate film such as a plastic film. It is preferable that the pressure-sensitive adhesive film further has a release film provided on the surface opposite to the surface on which the base film is laminated to the pressure-sensitive adhesive layer.
[0099] Examples of the base film include polyester resins such as polyethylene terephthalate, polyolefins such as polyethylene, and polyurethanes.
[0100] Examples of methods for producing the above-mentioned adhesive film include (1) a method in which an adhesive composition is applied onto a base film, dried, a release film is laminated, and at least one of aging treatments is performed at room temperature or at an elevated temperature, and (2) a method in which an adhesive composition is applied onto a release film, dried, a base film is laminated, and at least one of aging treatments is performed at room temperature or at an elevated temperature.
[0101] Such aging treatment is carried out to balance the adhesive properties as the reaction time of the chemical crosslinking of the adhesive, and the aging conditions are usually a temperature of 20 to 70°C and a time of 1 to 30 days, and specifically, for example, 23°C for 3 to 10 days or 40°C for 1 to 7 days.
[0102] When applying the pressure-sensitive adhesive composition, it is preferable to dilute the pressure-sensitive adhesive composition with a solvent before application. The dilution concentration is preferably such that the heating residue (solid content concentration) is 5 to 60% by weight, and particularly preferably 10 to 30% by weight.
[0103] The solvent is not particularly limited as long as it dissolves the pressure-sensitive adhesive composition, and examples of the solvent that can be used include ester solvents such as methyl acetate, ethyl acetate, methyl acetoacetate, and ethyl acetoacetate, ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, aromatic solvents such as toluene and xylene, and alcohol solvents such as methanol, ethanol, and propyl alcohol. Among these, ethyl acetate and methyl ethyl ketone are preferably used in terms of solubility, drying property, cost, etc. These may be used alone or in combination of two or more kinds.
[0104] The pressure-sensitive adhesive composition can be applied by a conventional method such as roll coating, die coating, gravure coating, comma coating, or screen printing.
[0105] In addition, the above-mentioned adhesive film is aged at 40°C for 3 days, and then prepared into a 25 mm x 100 mm test piece. The test piece is pressed and attached to a stainless steel plate (SUS304BA plate) whose surface has been wetted with purified water using a 2 kg rubber roller in two passes at 23°C and a relative humidity of 50%. The test piece is then left to stand in the same atmosphere for 30 minutes, and the adhesive strength when peeled off at a peel angle of 180° and a peel speed of 300 mm / min is preferably 5.0 N / 25 mm or more, and more preferably 7.0 N / 25 mm or more.
[0106] The pressure-sensitive adhesive film of the present invention is used by laminating the pressure-sensitive adhesive layer surface to the surface of an adherend, either directly or, in the case of a film having a release film, after removing the release film.
[0107] The adhesive film of the present invention shows sufficient adhesive performance even under water or wet conditions, and furthermore, when it is peeled off after being adhered to an adherend, it is possible to prevent the occurrence of adhesive residue and sticking marks on the surface of the adherend, so it is also excellent in the resistance to contamination of the adherend. Therefore, it can be suitably used as an adhesive film for various members such as a surface protection film, a display label, a masking tape, an adhesive film for a touch panel, an adhesive film for a sensor such as ITO, an adhesive film for an in-vehicle use, an optical film, and a polarizing plate, and is particularly suitable for use as an adhesive film for masking, particularly as a masking tape (masking tape) for construction. EXAMPLES
[0108] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by weight.
[0109] First, the following materials were prepared prior to the experiment.
[0110] <Acrylic resin> Acrylic resins (A-1) to (A-13) and (A'-1) were prepared according to the preparation methods described below. The composition and physical properties of each acrylic resin are shown in Table 1 below. The weight average molecular weight (molecular weight Mw), dispersity, and glass transition temperature (Tg) of the above acrylic resin shown in Table 1 were measured according to the above-mentioned methods. The viscosity shown in Table 1 was measured according to the viscometer method using a Brookfield type rotational viscometer in accordance with JIS K7117-1 (1999). The monomers (1-a) to (1-e) prepared as materials for each acrylic resin are represented by the following chemical formula.
[0111] [ka]
[0112] [ka]
[0113] [ka]
[0114] [ka]
[0115] [ka]
[0116] The above monomers (1-a) to (1-e) were synthesized as follows.
[0117] [Synthesis of Monomer (1-a)] After attaching a dropping funnel to a three-necked flask containing a rotor, 2-hydroxyethyl methacrylate (95.0 g, 0.73 mol) was placed in the flask and dissolved in tetrahydrofuran (1000 mL), and triethylamine (89.2 g, 0.88 mol) was added. The mixture thus obtained was cooled to 0°C, and then methanesulfonyl chloride (101.5 g, 0.89 mol) was placed in the dropping funnel and slowly dropped into the mixture. After the dropwise addition, the mixture was reacted at 25°C for 16 hours. Next, water (800 mL) was added to the mixture after the reaction, and the product was extracted into the organic layer with ethyl acetate (800 mL x 3 times). The ethyl acetate solution was washed with water (800 mL) and brine (800 mL) in that order, and dehydrated with anhydrous sodium sulfate. Then, the solvent was removed with an evaporator to obtain methanesulfonic acid-2-ethyl methacrylate (yellow liquid, 151.0 g).
[0118] In addition, the above-mentioned yellow liquid 1 The results of analysis by 1 H NMR were as follows: 1 H NMR (400MHz, CDCl3): δ=6.08(s, 1H), 5.57-5.54(m, 1H), 4.41-4.37(m, 2H), 4.35-4.31(m, 2H), 2.98(s, 3H), 1.88(s, 3H)
[0119] In addition, a three-neck flask equipped with a rotor was charged with gallic acid (36.0 g, 0.21 mol) and sodium hydrogen carbonate (43.0 g, 0.51 mol), and DMSO (300 mL) was added to prepare a mixture. The methanesulfonic acid-2-ethyl methacrylate (36.7 g, 0.18 mol) obtained as above was added thereto at room temperature, and the mixture was reacted at 80° C. for 16 hours. The reaction solution was returned to room temperature, water (300 mL) and 1N hydrochloric acid solution (70 mL) were added, and the product was extracted into the organic layer with ethyl acetate (400 mL x 3 times). The ethyl acetate solution was washed with water (400 mL) and brine (500 mL) in that order, and dehydrated with anhydrous sodium sulfate. The solvent was then removed with an evaporator, and the product was purified by column chromatography (packing material: silica gel, solvent: hexane / ethyl acetate mixture), and further recrystallized with a solution of ethyl acetate / n-heptane = 1 / 8 (270 mL) to obtain monomer (1-a) (white solid, 26.0 g).
[0120] In addition, the above-mentioned white solid 1 The results of analysis by 1 H NMR were as follows: 1 H NMR (400MHz, DMSO-d6): δ=9.22(s, 3H), 6.94(s, 2H), 6.05-6.02(m, 1H), 5.71-5.67(m, 1H), 4.46-4.36(m, 4H), 1.87(t, 3H)
[0121] [Synthesis of Monomer (1-b)] After attaching a dropping funnel to a three-necked flask containing a rotor, 4-(chloroacetyl)catechol (75.0 g, 0.40 mol) and methacrylic acid (76.1 g, 0.88 mol) were placed in the flask and dissolved in acetonitrile (1200 mL). The mixture thus obtained was cooled to 0°C, and then triethylamine (85.4 g, 0.84 mol) was placed in the dropping funnel and slowly dropped into the mixture under a nitrogen stream. After dropping, the mixture was reacted at 80°C for 20 hours. The mixture after the reaction was returned to room temperature, a 2N aqueous hydrochloric acid solution was added until the pH reached 4, water (1000 mL) was added, and the product was extracted into an organic layer with dichloromethane (1100 mL x 2). The dichloromethane solution was dehydrated with anhydrous sodium sulfate, the solvent was removed with an evaporator, and the product was purified by column chromatography (packing material: silica gel, solvent: hexane / ethyl acetate mixture) to obtain monomer (1-b) (white solid, 46.7 g).
[0122] In addition, the above-mentioned white solid 1 The results of analysis by 1 H NMR were as follows: 1 H NMR (400MHz, DMSO-d6): δ=10.45-9.27(m, 2H), 7.43-7.28(m, 2H), 6.84(d, 1H), 6.12(s, 1H), 5.77(t, 1H), 5.42(s, 2H), 1.93(s, 3H)
[0123] [Synthesis of monomer (1-c)] After attaching a dropping funnel to a three-necked flask containing a rotor, sodium bicarbonate (40.0 g, 0.48 mol) and sodium tetraborate decahydrate (100.6 g, 0.26 mol) were placed in the flask, dissolved in water (1000 mL), and nitrogen bubbling was performed for 1 hour. After that, dopamine hydrochloride (50.0 g, 0.26 mol) was added, and a mixture of methacrylic anhydride (52.8 g, 0.34 mol) and tetrahydrofuran (250 mL) was placed in the dropping funnel and slowly dropped at room temperature. After dropping, 1N aqueous sodium hydroxide solution was added to the reaction solution to adjust the pH to 8, and the reaction was performed at 20 ° C for 34 hours while bubbling nitrogen. Next, the reaction solution was filtered under reduced pressure at room temperature, and the filtrate was washed with ethyl acetate (150 mL x 2 times). After washing, 1N hydrochloric acid was added to the aqueous solution until the pH became 2, and the product was extracted into the organic layer with ethyl acetate (500 mL x 3 times). The ethyl acetate solution was dehydrated with anhydrous sodium sulfate, and the solvent was distilled off under reduced pressure until the volume was about 200 mL. Then, hexane (500 mL) was added, and precipitation by recrystallization (0 ° C, 4 hours) was performed. The precipitate was filtered and washed twice with a mixed solution of ethyl acetate / n-heptane = 1 / 10 (20 ° C, immersion for 10 hours). Furthermore, recrystallization was performed twice with a solution of isopropanol / n-heptane = 5 / 1 (2000 mL) to obtain monomer (1-c) (white solid, 42.3 g).
[0124] In addition, the above-mentioned white solid 1 The results of analysis by 1 H NMR were as follows: 1 H NMR(400MHz,DMSO-d6): δ=8.78-8.73(m, 1H), 8.66-8.61(m, 1H), 7.94(t, 1H), 6.62(d, 1H), 6.57(d, 1H), 6.42 (dd, 1H), 5.61(s, 1H), 5.29(t, 1H), 3.25-3.18(m, 2H), 2.58-2.53(m, 2H), 1.83(s, 3H)
[0125] [Synthesis of monomer (1-d)] 3,4-Dihydroxybenzoic acid (71.1 g, 0.46 mol) and DMSO (550 mL) were placed in a three-neck flask equipped with a rotor, and methanesulfonic acid-2-ethyl methacrylate (80.0 g, 0.38 mol) obtained by the same method as in the synthesis process of the acrylic monomer (1-a) and sodium hydrogen carbonate (93.6 g, 1.11 mol) were added in that order at room temperature, and the mixture was allowed to react at 80°C for 16 hours. The reaction solution was returned to room temperature, water (500 mL) was added, and the mixture was stirred for 3 minutes. The product was then extracted into the organic layer with ethyl acetate (300 mL x 4 times). The ethyl acetate solution was washed with brine (200 mL x 2 times) and dehydrated with anhydrous sodium sulfate. Then, 2,6-di-tert-butyl-4-methylphenol (10 mg) was added as a polymerization inhibitor, the solvent was removed with an evaporator, and recrystallization was performed (slowly cooled from 85 ° C to 0 ° C) with a solution of acetonitrile / n-heptane = 10 / 1 (88 mL) to obtain monomer (1-d) (white solid, 64.3 g).
[0126] In addition, the above-mentioned white solid 1 The results of analysis by 1 H NMR were as follows: 1 H NMR (400MHz, DMSO-d6): δ=9.59(s, 2H), 7.38-7.24(m, 2H), 6.82-6.80(d, 1H), 6.03(s, 1H), 5.68(s, 1H), 4.48-4.36(m, 4H), 1.86(s, 3H)
[0127] [Synthesis of monomer (1-e)] In a three-necked flask equipped with a rotor and a dropping funnel, 3,4-dihydroxybenzaldehyde (100.0 g, 0.72 mol) and pyridinium p-toluenesulfonate (181.9 g, 0.72 mol) were placed and dissolved in dichloromethane (1000 mL). After cooling the reaction solution to 0°C, ethyl vinyl ether (114.9 g, 1.59 mol) was placed in the dropping funnel and slowly dropped. After dropping, the reaction solution was reacted at 25°C for 16 hours. The reaction mixture was added with tert-butyl methyl ether (1000 mL) and washed with brine (800 mL). The aqueous layer was washed with tert-butyl methyl ether (500 mL x 2 times), and the resulting organic layers were combined, washed with 1N aqueous sodium hydroxide solution (1000 mL), and dehydrated with anhydrous sodium sulfate. The solvent was then removed with an evaporator to obtain 3,4-bis(1-ethoxyethoxy)benzaldehyde (brown oily liquid, 172.0 g).
[0128] In addition, the above-mentioned brown oily liquid 1 The results of analysis by 1 H NMR were as follows: 1 H NMR(400MHz,CDCl3): δ=9.84(s, 1H), 7.56(t, 1H), 7.48(dt, 1H), 7.21(dd, 1H), 5.50(qd, 1H), 5.42-5.35 (m, 1H), 3.90-3.74(m, 2H), 3.63-3.50(m, 2H), 1.56-1.48(m, 6H), 1.23-1.15(m, 6H)
[0129] Next, the above 3,4-bis(1-ethoxyethoxy)benzaldehyde (86.0 g, 0.30 mol) was placed in a three-neck flask equipped with a rotor and dissolved in tetrahydrofuran (900 mL). After the reaction solution was cooled to 0°C, sodium borohydride (12.7 g, 0.34 mol) was gradually added. After all the sodium borohydride was added, the reaction solution was reacted at 25°C for 16 hours. At room temperature, saturated ammonium chloride water (420 mL) was added little by little to the reaction solution, and the precipitate was filtered off. The organic solvent in the filtrate was removed using an evaporator, and the product was extracted with dichloromethane (800 mL x 2). The dichloromethane solution was washed with brine (1000 mL) and dehydrated with anhydrous sodium sulfate. The solvent was then removed using an evaporator to obtain 3,4-bis(1-ethoxyethoxy)benzyl alcohol (yellow oily liquid, 85.3 g).
[0130] In addition, the above-mentioned yellow oily liquid 1 The results of analysis by 1 H NMR were as follows: 1 H NMR(400MHz,CDCl3): δ=7.10-7.03(m, 2H), 6.93(dt, 1H), 5.38-5.30(m, 2H), 4.58(s, 2H), 3.8 9-3.79(m, 2H), 3.62-3.51(m, 2H), 1.50-1.47(m, 6H), 1.23-1.16(m, 6H)
[0131] A dropping funnel was attached to a three-necked flask containing a rotor, and the above 3,4-bis(1-ethoxyethoxy)benzyl alcohol (85.0 g, 0.30 mol), triethylamine (60.5 g, 0.60 mol) and 4-dimethylaminopyridine (3.7 g, 0.03 mol) were placed in the flask and dissolved in tetrahydrofuran (800 mL). Then, methacrylic anhydride (55.3 g, 0.36 mol) was placed in the dropping funnel and slowly dropped under a nitrogen stream. After dropping, the reaction solution was reacted at 25°C for 16 hours. After the reaction, the solvent was removed using an evaporator, and the residue was purified using column chromatography (filler: silica gel, solvent: petroleum ether / ethyl acetate mixture) to obtain a 1-ethoxyethoxy protected monomer (1-e) (white solid, 58.5 g).
[0132] In addition, the above-mentioned white solid 1 The results of analysis by 1 H NMR were as follows: 1 H NMR(400MHz,CDCl3): δ=7.12(d, 1H), 7.06(d, 1H), 6.99-6.95(m, 1H), 6.14(s, 1H), 5.60-5.56(m, 1H), 5.40-5.30(m, 2H), 5 .11(s, 2H), 3.91-3.77(m, 2H), 3.64-3.53(m, 2H), 1.96(s, 3H), 1.54-1.46(m, 6H), 1.24-1.17(m, 6H)
[0133] The 1-ethoxyethoxy-protected monomer (1-e) (100.0 g, 0.28 mol) was placed in a three-neck flask equipped with a rotor and dissolved in methanol (600 mL). Pyridinium p-toluenesulfonate (14.3 g, 0.06 mol) was then added and reacted at 25° C. for 40 minutes. After the reaction, the solvent was removed using an evaporator (water bath temperature 35° C.), and the product was purified by column chromatography (packing material: silica gel, solvent: n-heptane / ethyl acetate mixture) to obtain monomer (1-e) (white solid, 33.5 g).
[0134] In addition, the above-mentioned white solid 1 The results of analysis by 1 H NMR were as follows: 1 H NMR (400MHz, CDCl3): δ=6.92(d, 1H), 6.88-6.81(m, 2H), 6.16(s, 1H), 6.04-5.75(m, 3H), 5.09(s, 2H), 1.96(s, 3H)
[0135] [Preparation of acrylic resin (A-1)] In a four-necked round-bottom flask equipped with a reflux condenser, a stirrer, a nitrogen gas inlet, and a thermometer, 1 part of monomer (1-a) (acrylic monomer (a1)), 8 parts of acrylic acid (AAc) (copolymerizable monomer (a2)), and 91 parts of n-butyl acrylate (BA) ((meth)acrylic acid alkyl ester monomer (a3)) were charged as copolymerization components (monomers) of acrylic resin (A-1), and further 45 parts of methyl ethyl ketone, 45 parts of acetone, and 0.038 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator were charged, and the temperature was raised with stirring, and the internal temperature was raised to the boiling point to start the reaction. Next, 33.8 parts of a methyl ethyl ketone solution containing 0.023% AIBN was dropped over 2 hours. Furthermore, during the polymerization, a mixed solution of 33.8 parts of methyl ethyl ketone and 0.023 parts of AIBN and a mixed solution of 25 parts of methyl ethyl ketone and 0.015 parts of AIBN were successively added and reacted under reflux for 7.5 hours to obtain a solution of acrylic resin (A-1).
[0136] [Preparation of acrylic resins (A-2) to (A-6), (A-10) to (A-13)] The types and ratios of the monomers (a1) to (a3) were changed so as to obtain an acrylic resin having a monomer composition as shown in Table 1. Other than that, polymerization was carried out in accordance with the preparation method of the acrylic resin (A-1) to obtain a solution of the desired acrylic resin.
[0137] [Preparation of acrylic resins (A-7) to (A-9)] The types and ratios of the monomers (a1) to (a3) were changed so as to obtain an acrylic resin having the monomer composition shown in Table 1 below, and acetone was changed to methanol. Polymerization was otherwise carried out in accordance with the preparation method for the acrylic resin (A-1) above, to obtain a solution of the desired acrylic resin.
[0138] [Preparation of acrylic resin (A'-1)] In a reactor equipped with a thermometer, a stirrer, a dropping funnel and a reflux condenser, 61.3 parts of ethyl acetate and 0.037 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged, and the internal temperature was raised to the boiling point while stirring, and then a mixed liquid in which 8 parts of acrylic acid (AAc) (copolymerizable monomer (a2)), 0.1 parts of 2-hydroxyethyl methacrylate (HEMA) (copolymerizable monomer (a2)) and 91.9 parts of n-butyl acrylate (BA) ((meth)acrylic acid alkyl ester monomer (a3)) were mixed and dissolved, which are copolymerization components (monomers) of the acrylic resin (A'-1), was dropped over 2 hours. Furthermore, during the polymerization, 0.08 parts of AIBN was added to 13.3 parts of toluene, and the mixture was reacted under reflux for 6.0 hours, and then diluted with 90.68 parts of ethyl acetate and 2.03 parts of toluene to obtain a solution of the acrylic resin (A'-1).
[0139] [Table 1]
[0140] <Epoxy-based crosslinking agent (B)> Multifunctional epoxy resin (B-1): TETRAD-C (manufactured by Mitsubishi Gas Chemical Company, Inc.)
[0141] [Example 1] [Preparation of Pressure-Sensitive Adhesive Composition] 0.1 part of an epoxy-based crosslinking agent (B-1) was mixed with 100 parts of the solid content of the acrylic resin (A-1) obtained above to prepare a pressure-sensitive adhesive composition.
[0142] [Preparation of adhesive film] The adhesive composition prepared above was applied to a PET film (thickness 38 μm) substrate so that the adhesive layer would have a thickness of about 25 μm after drying, and then dried for 2 minutes at 100° C. Thereafter, a release-treated PET film (release film: thickness 38 μm) was attached to the coated surface to protect the adhesive layer, and an adhesive film was produced. The obtained adhesive film was evaluated for the following properties, and the results are shown in Table 2 below.
[0143] <Adhesive strength> (Adhesion to dry surfaces) The adhesive film obtained above was aged at 40°C for 3 days, and then prepared into a 25mm x 100mm test piece. The release film was peeled off, and the piece was pressed and attached to a stainless steel plate (SUS304BA plate) with a 2kg rubber roller in two passes at 23°C and 50% relative humidity. After leaving the piece to stand for 30 minutes in the same atmosphere, the 180° peel strength (N / 25mm) was measured at a peel speed of 300mm / min.
[0144] (Adhesion to wet surfaces) The adhesive film obtained above was aged at 40°C for 3 days, and then prepared into a 25mm x 100mm test piece. The release film was peeled off, and the surface was wetted with purified water and pressed and attached to a stainless steel plate (SUS304BA plate) with a 2kg rubber roller in two passes at 23°C and 50% relative humidity. After leaving it to stand for 30 minutes in the same atmosphere, the 180° peel strength (N / 25mm) was measured at a peel speed of 300mm / min, and evaluated according to the following criteria. (Evaluation Criteria) ○...7.0N / 25mm or more △ 5.0N / 25mm or more, less than 7.0N / 25mm ×...Less than 5.0N / 25mm
[0145] <Stain resistance> (Resistance to stains on wet surfaces) The adhesive film obtained above was aged at 40°C for 3 days, and then prepared into a 25mm x 100mm test piece. The release film was removed, and the surface was pressed and attached to a stainless steel plate (SUS304BA plate) with a surface wetted with purified water using a 2kg rubber roller in two passes at 23°C and a relative humidity of 50%. After leaving the film to stand for 30 minutes in the same atmosphere, the state of the adherend surface after 180° peeling at a peeling speed of 300mm / min was observed and evaluated according to the following criteria. (Evaluation Criteria) ○: No adhesive residue was observed ×: Adhesive residue was observed
[0146] [Examples 2 to 13, Comparative Example 1] Pressure-sensitive adhesive compositions were prepared and pressure-sensitive adhesive films were produced in the same manner as in Example 1, except that the acrylic resins shown in Table 2 below were used. Using the obtained pressure-sensitive adhesive compositions and pressure-sensitive adhesive films, evaluations were carried out in the same manner as in Example 1. The results are also shown in Table 2 below.
[0147] [Table 2]
[0148] The results in Table 2 above show that the examples have excellent adhesion to wet surfaces, whereas the comparative examples, which used acrylic resins that did not contain monomers of a specific structure as copolymerization components, had poor adhesion to wet surfaces. This also shows that it is important that the acrylic resin contains a monomer having a specific structure as a copolymerization component.
[0149] Furthermore, the adhesive compositions of the examples also have good resistance to contamination on wet surfaces, and are therefore suitable for use as adhesives for masking films and masking adhesive films. [Industrial Applicability]
[0150] The adhesive obtained from the adhesive composition using the acrylic resin of the present invention can provide an adhesive composition that can exhibit sufficient adhesive performance even in water or under wet conditions. Therefore, it can be suitably used as an adhesive for various members such as an adhesive for masking films, an adhesive for surface protection films, an adhesive for display labels, an adhesive for masking tapes, etc., and is particularly suitable for use as an adhesive for masking films, particularly as an adhesive for architectural masking films.
Claims
1. The acrylic resin (A) is obtained by copolymerizing a copolymerization component (a) containing 0.01 to 50% by weight of an acrylic monomer (a1) represented by the following chemical formulas (1-a), (1-b), and (1-d), 0.1 to 30% by weight of a copolymerizable monomer (a2) having a hydroxyl group and / or a carboxyl group excluding the above (a1), and 40 to 99% by weight of a (meth)acrylic acid alkyl ester monomer (a3) having an alkyl group having 1 to 20 carbon atoms. 【Chemistry 1】
2. The acrylic resin (A) according to claim 1, wherein the copolymerizable monomer (a2) having a hydroxyl group and / or a carboxyl group is (meth)acrylic acid and / or a (meth)acrylate monomer.
3. A pressure-sensitive adhesive composition comprising the acrylic resin (A) according to claim 1 or 2 and a crosslinking agent (B).
4. A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition according to claim 3.
5. An adhesive film comprising an adhesive layer comprising the adhesive according to claim 4.
6. A masking adhesive comprising the adhesive according to claim 4.
7. A masking adhesive film comprising an adhesive layer made of the adhesive according to claim 4.
Citation Information
Patent Citations
Fluorescent electronic protective paint and preparation method thereof
CN107805434A
Photopolymerizable composition, photopolymerizable planographic printing plate and image forming method using the same
JP2003255532A
Water dispersion-type adhesive composition and adhesive product
JP2003313525A
Novel polymer
JP2012233059A
Adhesive sheet for wet surfaces, and concrete structure
JP2017160344A